Prūsų kalbos veiksmažodžių struktūros ypatumai - Kaukienė, Audronė (Baltistica, 1998)
PECULIARITIES OF VERB STRUCTURE IN OLD PRUSSIANTwo types of verbs with a suffix variation have been reconstructed on the basis of Old Prussian catechisms.Verbs of type 1 have the suffix -ī- in the Infinitive and its derivatives (the vowel ī in the dialects of the catechisms is slightly diphthongized, pronounced as eī and recorded as ī, ij, ei, i), and the suffixes -ē- and -ā- in the Present and Past tenses, e.g. billīt, billītwei  ‘to speak’, billīton ‘is said’, bille ‘I speak, you speak, he speaks’, billē / billā, billa ‘speaks’, billēmai ‘we speak’, billai ‘I spoke’, billa, byla, bela, billāts, belats, bilats, bylaczt / billē ‘he spoke’.Verbs of this type can correspond to verb forms with different structures in East Baltic languages or have no correspondences at all. In the linguistic literature the suffix -ī- of the Infinitive is usually presented as being derived from *-ē- on the basis of the theoretically reconstructed thematic stems of the Present and Past tenses. Yet the existing materials do not support this kind of reconstruction,Verbs of type 2 have the suffix *-ē- in the Infinitive and its derivatives (the vowel ē in the dialects of the catechisms became narrower and was pronounced almost as ī), and the suffix -ī̆- at the end of the Present tense stem (the Past tense forms have not been recorded); e.g. turīt, turrit, turrītwei, turrettwey, turryetwei (*tur-ē-) ‘to have’, turri ‘I have’, tur, turri, turei ‘you have’, turri, turei, turret,ture ‘he has, they have’, turrimai ‘we have’, turriti ‘you have’. In East Baltic languages their equivalents are i-stem verbs with the suffix -ē- in the Infinitive.Type 1 is very copious and productive, while type 2 ought to be considered a relic. Yet the dominance of type 1 should be accounted for not by phonological, but rather by morphological reasons, as in live Old Prussian *ē > ī and *i > eī could not have merged.
Keywords: prūsų kalba; veiksmažodis